Trauma Disrupts Reinforcement Learning in Rats—A Novel Animal Model of Chronic Stress Exposure - Bielawski, Tomasz; Drapała, Jarosław; Krowicki, Paweł; Stańczykiewicz, Bartłomiej; Frydecka, Dorota (Frontiers in Behavioral Neuroscience, 2022)
Trauma, as well as chronic stress that characterizes a modern fast-paced lifestyle, contributes to numerous psychopathologies and psychological problems. Psychiatric patients with traumas, as well as healthy individuals who experienced traumas in the past, are often characterized by diminished cognitive abilities. In our protocol, we used an animal model to explore the influence of chronic trauma on cognitive abilities and behavior in the group of 20 rats (Rattus norvegicus). The experimental group was introduced to chronic (12 consecutive days) exposure to predator odor (bobcat urine). We measured the reinforcement learning of each individual before and after the exposition via the Probabilistic Selection Task (PST) and we used Social Interaction Test (SIT) to assess the behavioral changes of each individual before and after the trauma. In the experimental group, there was a significant decrease in reinforcement learning after exposure to a single trauma (Wilcoxon Test, p=0.034 ) as well as after 11 days of chronic trauma (Wilcoxon-test, p= 0.01) in comparison to pre-trauma performance. The control group, which was not exposed to predator odor but underwent the same testing protocol, did not present significant deterioration in reinforcement learning. In cross-group comparisons, there was no difference between the experimental and control group in PST before odor protocol (U Mann-Whitney two-sided, p=0.909). After exposure to chronic trauma, the experimental group deteriorated in PST performance compared to control (U Mann-Whitney Two-sided, p=0.0005). In SIT, the experimental group spent less time in an Interaction Zone with an unfamiliar rat after trauma protocol (Wilcoxon two-sided test, p=0.019). Major strengths of our models are: 1.) protocol allows investigating reinforcement learning before and after exposition to chronic trauma, with the same group of rats 2.) translational scope, as the PST is displayed on touchscreen, similarly to human studies 3.) protocol delivers chronic trauma that impairs reward learning, but behaviorally does not induce full-blown anhedonia, thus rats performed voluntarily throughout all the procedures.